Evaluation of the Quality of Primary Health Care Services for Adolescents With Chronic Illness in Kirkuk City (Medico Legal Update, 2020)
Background: Providing interventions, and implementing of best-practice care for patients with chronicdiseases is of greatest challenges currently facing primary care providers. This study aimed to evaluate thequality of primary health care(PHC)services for adolescents with chronic diseases in Kirkuk city.Methodology: A descriptive (quantitative design) was conducted through (18) primary health care centers(PHCCs) in Kirkuk city. A questionnaires was designed for the purpose of the study. A simple randomsample of organization structure PHC services (18) health professional were selected through the use ofprobability sampling approach. Data were analyzed is performed through the use of descriptive statisticaldata analysis approach. Results: The overall evaluation of quality of PHC services in Kirkuk city is adequate on (77.7 % : N=14),fair on (16.7 % :N=3) and Inadequate on (5.6%: N=1 ) .Domains such as quality of health service representhigh mean of scores on its items, Except on 2 items of Tangibles and on items of Responsiveness 2 on fromthe quality of PHC are low.Conclusion: The study indicates that the quality of PHC services does not execute impact upon adolescents’health status. This study depict that the evaluate of the quality of PHC services is adequate relative to all ofits dimensions of general health status, tangibles, accreditation, responsiveness, assurance and empathy.